1978
DOI: 10.1530/acta.0.0870279
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum TSH Level After Intraventricular Injection of Various Neuromediators in Rats

Abstract: The influence of various neuromediators on pituitary TSH secretion in rats has been investigated. Noradrenaline 50 \g=m\g/rat,dopamine 50 \g=m\g/rat, serotonine-creatinine-sulphate 100 \g=m\g/rat,gamma-aminobutyric acid 100 \g=m\g/rat,pilocarpine 1 mg/rat, histamine 100 \g=m\/rat were administered into the lateral ventricle of the brain. All agents were dissolved in Parker's fluid. Two control groups of animals were given Parker's fluid and subjected to surgical manipulations, respectively. Plasma TSH level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…There are many reports concerning the effects of amines, peptides and prostaglan dins (PGs) on thyrotoropin (TSH) secretion [1,2,4,7,9,10,12,13,19,21,23,[26][27][28][29][30][31][32][33], Substance P (SP), PG D2 and angiotensin II are found in the hypothalamus in rats [3,8,10,13,15], suggesting that they may affect thyrotropin-releasing hormone (TRH) and TSH secretion. A few studies have been made on the role of the cholinergic system in TSH secretion [1,10,12,21], Therefore, the authors investigated the effects of SP, angio tensin II, PG D2 and oxotremorine, a cholin ergic agonist, on TRH and TSH release in rats and have studied the possible mecha nism by which these substance exert their effect on TRH and TSH release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports concerning the effects of amines, peptides and prostaglan dins (PGs) on thyrotoropin (TSH) secretion [1,2,4,7,9,10,12,13,19,21,23,[26][27][28][29][30][31][32][33], Substance P (SP), PG D2 and angiotensin II are found in the hypothalamus in rats [3,8,10,13,15], suggesting that they may affect thyrotropin-releasing hormone (TRH) and TSH secretion. A few studies have been made on the role of the cholinergic system in TSH secretion [1,10,12,21], Therefore, the authors investigated the effects of SP, angio tensin II, PG D2 and oxotremorine, a cholin ergic agonist, on TRH and TSH release in rats and have studied the possible mecha nism by which these substance exert their effect on TRH and TSH release.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been made on the role of the cholinergic system in TSH secretion [1,10,12,21], Therefore, the authors investigated the effects of SP, angio tensin II, PG D2 and oxotremorine, a cholin ergic agonist, on TRH and TSH release in rats and have studied the possible mecha nism by which these substance exert their effect on TRH and TSH release.…”
Section: Introductionmentioning
confidence: 99%
“…Data from animal studies support both stimulatory and inhibitory roles for this neurotransmitter. Stimulation of TSH release by 5-HT has been suggested in studies em ploying intraventricular injection of 5-HT [17,18,39] and intraventricular and parenteral administration of the 5-HT precursor 5-hydroxytryptophan (5-HTP) [5,32] and the 5-HT synthesis inhibiting p-chlorophenylalanine [5,33], Con versely, inhibition of TSH release by 5-HT has been sugges ted in studies employing inirahypothalamic implants or in traventricular injection of 5-HT [15,23] and intraventricular or parenteral administration of the 5-HT agonist quipazine [19], the 5-HT-releasing ¿/-fenfluramine [8,9], the 5-HT pre cursor tryptophan [22,24,25], and p-chlorophenylalanine [31]. Further, studies employing 5-HTP suggest that 5-HT inhibits cold-induced activation of TSH [27,37].…”
mentioning
confidence: 99%
“…In fact, literature data (Holak et al, 1978;Jordan et al, 1978) have demonstrated that 5-HT causes hypersecretion of hypophyseal TSH, which, in turn, causes an increase in thyroid-hormone release. Our results confirm these data, since, throughout the treatment, 5-HT significantly increased TSH plasma levels.…”
Section: Discussionmentioning
confidence: 99%